1982
DOI: 10.1093/ajcn/36.5.910
|View full text |Cite
|
Sign up to set email alerts
|

A method for assessing carbohydrate energy absorption and its application to premature infants

Abstract: A method was developed for assessing indirectly the fecal excretion of carbohydrate-derived energy. Then, eight healthy premature infants (28 to 32 wk gestation, postnatal age 12 to 30 days) were randomly assigned to receive one of two formulas that differed only in the carbohydrate source: 100% lactose or 50% lactose: 50% glucose polymer (lactose + glucose polymer). Excreta collections were analyzed for total nitrogen, urea nitrogen, ammonia, fat, and total energy. Carbohydrate energy absorption was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
2
16
1
Order By: Relevance
“…However, there was a wide variation among subjects in the measured colonic fermentation of unabsorbed carbohydrate. Studies by Kien et al (1982) with preterm infants suggested that only about 10% of energy derived from lactose or a combination (50:50) of lactose and glucose polymers was excreted in the feces. In a later study, Kien et al (1987) presented evidence for extensive colonic fermentation of carbohydrates in infants fed a combined lactose and glucose polymer formula; however, doubling the lactose concentration of the formula (and eliminating glucose polymers from the formula) caused a doubling of the expired hydrogen value.…”
Section: Nonlactose Dietary Carbohydrates: Glucose Polymers and Maltosementioning
confidence: 99%
See 2 more Smart Citations
“…However, there was a wide variation among subjects in the measured colonic fermentation of unabsorbed carbohydrate. Studies by Kien et al (1982) with preterm infants suggested that only about 10% of energy derived from lactose or a combination (50:50) of lactose and glucose polymers was excreted in the feces. In a later study, Kien et al (1987) presented evidence for extensive colonic fermentation of carbohydrates in infants fed a combined lactose and glucose polymer formula; however, doubling the lactose concentration of the formula (and eliminating glucose polymers from the formula) caused a doubling of the expired hydrogen value.…”
Section: Nonlactose Dietary Carbohydrates: Glucose Polymers and Maltosementioning
confidence: 99%
“…Data were reviewed (see Appendix A) that suggested that fractional fat absorption in preterm infants fed formula was approximately 90% (Kien et al, 1982;Kien et al, 1990a). In addition, evidence will be presented in this chapter that indicates that some of the potential dietary carbohydrate energy ingested by preterm infants is also not available to the infant because of incomplete digestion of lactose in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weighed aliquots of formula, 24-h pools of human milk and 72-h stool homogenates were lyophilized and then submitted to calorimetric analysis (20). Losses of energy in the urine have been estimated from excreted urea and carbohydrate and correspond to 0.86 kcal/kg/day (2 1).…”
Section: Methodsmentioning
confidence: 99%
“…Our studies of lactose digestion and lactose fermentation in preterm infants suggested that Ͼ 50% of lactose might reach the colon (ie, malabsorbed) without causing diarrhea or significantly affecting weight gain or N balance. [7][8][9][10] However, in these studies, the degree of disaccharide maldigestion was assessed using stable isotope tracer techniques or breath H 2 studies. As a further test of the hypothesis that small intestinal malabsorption of even 50% of dietary disaccharide will not cause diarrhea nor appreciably affect growth, we constructed the experiment described in this paper in which lactulose was substituted for lactose at a level equal to 50% of the lactose concentration.…”
mentioning
confidence: 99%